Resilience and Cognitive Bias in Chinese Male Medical Freshmen - Peng, Li; Cao, Hong-Wen; Yu, Yongju; Li, Min (Frontiers in Psychiatry, 2017)
Background: Psychological resilience has become a hot issue in positive psychology research. However, little is known about cognitive bias difference of individuals with different resilience levels. This study aimed to explore the characteristics of cognitive bias and its role in Chinese medical freshmen with different resilience levels. Methods: 312 Chinese medical freshmen were surveyed by the Chinese version of Connor-Davidson Resilience Scale (CD-RISC), 92 of whom were respectively allocated into high (n=46) and low (n=46) resilient group to complete computerized tests using an attention shifting task and an emotional picture recognition task. Results: All participants had the highest recognition accuracy towards negative pictures compared to neutral and positive ones. By comparison, it was found that the high-resilient group had a longer recognition response time towards positive emotional pictures, but a shorter response time towards negative emotional pictures, while the low-resilient group had a longer response time towards negative emotional pictures. Conclusion: This study pointed to the association between resilience and cognitive bias. Medical freshmen with different resilience levels showed significant differences in the cognitive bias towards emotional pictures, suggesting that reducing negative cognitive bias and promoting positive cognitive bias could be important targets to increase resilience.